Theoretical characteristics of the relation between urban housing and the state of health of its inhabitants - Hernández Pérez, Káteri Samantha (Benemérita Universidad Autónoma de Puebla, 2020)
The current document presents the bibliographic recovery and review from academicpostulates over health influence related to the characteristics of contemporary urban housing.The main objective from the authors frame on a coherent interpretation of recent theoreticaldocuments, which attempt to analyze the relationship between the architectural space ofhousing and its influence related to harmful consequences over health. Human health issuesare complex, does consist from multiple microsystems all interconnected; therefore, this textcharacterize the phenomenon: in the first instance, from a determinism focused on thedescription both physical and mental illnesses, and second their relation as a cause related to the consequences of inhabiting such a living space. This theoretical apparatus exposed is partof a current research, thus presenting an approximation of housing fundamentals related tothe problems and their impact on the health of its inhabitants.